Thermoregulatory Strategies of Diving Air-Breathing Marine Vertebrates: A Review - Favilla, Arina B.; Costa, Daniel P. (Frontiers in Ecology and Evolution, 2020)
The aquatic habitat of marine “air-breathing” vertebrates provides a significant thermoregulatory challenge due to the high thermal conductivity of water. In addition to temperature changes across their range, air-breathing vertebrates experience temperature changes on the timescale of seconds to minutes as they perform dives to access two critical resources: air at the surface and food at depth. In response to these challenges, air-breathing vertebrates have developed morphological and physiological adaptations that align with their life histories and phylogenies and contribute to homeostasis. However, the physiological and behavioral mechanisms used to maintain thermal balance while diving is still poorly understood. The cardiovascular system is integral to the physiological responses associated with the dive response, exercise, digestion, and thermoregulation. The adjustments required to meet one physiological demand may not be compatible with another and can result in a potential conflict between the various physiological demands imposed on air-breathing divers. We reviewed the literature on thermoregulation while diving in an effort to synthesize our current understanding of the thermoregulatory strategies of diving air-breathing marine vertebrates. Studies have demonstrated that thermoregulatory strategies can involve the temporal separation of two conflicting responses, a compromise in the performance of one response over another, or coordination of synergistic responses. We hope that a review and synthesis of both laboratory and field studies will stimulate future research efforts at the intersection of thermoregulation and diving physiology. Expanding the use of physiological biologgers, particularly to understudied species, will enhance our understanding of how these animals coordinate various physiological demands to maintain homeostasis in a thermally challenging environment.